Chief Physician Jingdong Xue used the Method of Tonifying Liver Qi Experience of Fatigue Due to Cancer After Liver Cancer Operation - Zhang, Tingting; Xue, Jingdong (Journal of Contemporary Medical Practice, 2024)
Liver cancer as a common malignant tumor, the incidence and fatality rate in the ranking of cancer in the forefront, seriously threatening the life and health of patients, the most common treatment is surgical treatment, including surgical resection, interventional therapy and radiofrequency ablation therapy, the common postoperative complications of cancer due to fatigue, seriously affect the quality of life of patients, Western medicine currently no treatment for this disease in fact, Chinese medicine has obvious advantages in this treatment. Now Jingdong Xue director of the use of tonifying liver qi treatment experience to make a summary.